Síntese do propionato de carvacrol e estudo de suas propriedades anti-hiperalgésica e anti-inflamatória em protocolos - Souza, Marília Trindade de Santana (2014)
Terpenes are naturally occurring compounds obtained from the plants secondary metabolism. Despite presenting pharmacological effects, structural changes within their skeleton may increasing their pharmacological activity and attenuate the toxicological effects. Carvacrol is a phenolic monoterpene present in essential oils from plants belonging to the Labiatae family. Studies have demonstrated that carvacrol has anti-inflammatory activity. However, sctructural changes may reduce the effective dose of this monoterpene. Thus, in this study, we conducted an extensive systematic review evaluating the antiinflammatory activity of terpenes that suffered an alteration in its structure through synthesis and semi-synthesis, synthesize the carvacrol propionate (CP) from the carvacrol and evaluate its potential antinociceptive, anti-hyperalgesic and anti-inflammatory effects. To build the revision, it was made the search in Scopus, Embase and PubMed databases, using the descriptors anti-inflammatory agents, terpenes and structure activity relationship. In the experimental part, it was used Male Swiss mice (25-35 g) with 2 to 3 months age. The animals were divided in groups and were treated with CP (25, 50 and 100 mg/kg), vehicle (saline solution 0.9% + Tween 80 0.2%) or standard drug, intraperitoneally (i.p.). The antinociceptive effect was evaluated through the formalin (1%) protocol and the hot plate test. The mechanical hyperalgesia was evaluated through the algic agents injection: carragee nan (CG; 300 µg/paw), tumor necrosis factor-a (TNF-a; 100 pg/paw), prostaglandin E2 (PGE2; 100 ng/paw) or dopamine (DA; 30 µg/paw) using a digital analgesimeter (von Frey). To assess the anti-inflammatory effect, it was used the pleurisy and paw edema induced by GC (1 %) in digital plethysmometer. The cytotoxicity of CP was evaluated by the MTT colorimetric method. The experimental protocols were approved by the UFS ethics committee (CEPA/UFS: 35/12). The results are expressed as mean ± SEM and differences between groups were analyzed by one-way or two-way ANOVA test followed by Tukey or Bonferroni tests. Values of p < 0.05 were considered statistically significant. In systematic review, 27 papers were found concerning about terpenes structural modification and the evaluation of their anti-inflammatory activity. In the experimental part, the administration of CP produced a significant decrease (p < 0.01 and 0.001) in the test formalin-induced nociceptive in both phases of the test. In the hot plate test, the reaction time increased significantly at doses 50 and 100 mg/kg (p < 0.05, 0.01 and 0.001). CP inhibited the development of mechanical hyperalgesic induced by all agents tested (p < 0.05, 0.01 and 0.001). In the evaluation of anti-inflammatory activity, the treatment with CP was able to decrease significantly the leukocyte recruitment (p < 0.001), the TNF-a (p < 0.001), the IL-1ß (p < 0.05) and protein leakage (p < 0.01). In addition, the paw edema induced by CG in mice was inhibited significantly by CP (p < 0.05, 0.01 and 0.001). Thus, it is concluded that the CP attenuates nociception, mechanical hyperalgesia and inflammation, through an inhibition of cytokines. Therefore, structural modification terpene can be an interesting alternative for obtaining molecules with pharmacological properties.